PENGARUH MODEL GAME BASED LEARNING BERBANTUAN PERMAINAN EDUKATIF EDUCAPLAY TERHADAP PENGUASAAN KOSAKATA BAHASA INGGRIS SISWA SEKOLAH DASAR - Nurbaiti, Nisrina; Indah Nurmahanani; Jennyta Caturiasari (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study stems from the main issue, namely the low English vocabulary mastery among elementary school students. One of the causes is the use of monotonous teaching methods that rely heavily on textbooks, which leads to student boredom during lessons. One way to address the issue of low English vocabulary mastery among elementary school students is by using a game-based learning model assisted by the educational game platform Educaplay. The game-based learning model aims to provide interactive and enjoyable learning through the use of games. The purpose of this study is to determine the effect of using a game-based learning model assisted by the Educaplay educational game on improving elementary school students' English vocabulary mastery. This research uses a quantitative method with a quasi-experimental design. The sample in this study consisted of students from classes IV B and IV C at SDIT Al-Bina Purwakarta, which served as the experimental and control groups, respectively. In this study, the experimental class received treatment using the game-based learning model assisted by the Educaplay educational game, while the control class received treatment using the discovery learning model assisted by instructional video media. Based on the results of the simple linear regression test, it can be concluded that the use of the game-based learning model assisted by the Educaplay educational game had a more significant positive effect on improving elementary school students' English vocabulary mastery.